KOMODIFIKASI DALAM TAYANGAN TELEVISI (Kajian Terhadap Program Indonesian Idol 2014) - Dionni Ditya Perdana (UNIVED PRESS, Universitas Dehasen Bengkulu, 2017)
Mass media at economi politikcal’s perspektive is an industrion. So the system media work is aimed at profit. One attempt to gain an advantage is add value to become the exchange rate, this is called commodification.This research will look at how the practice of the media to commodification, by taking the Indonesian Idol 2014 television program. Keywords : Economic Politikal Media, Comodification, Indonesian Idol, Television